Educação de jovens e adultos no interior da Bahia : programa REAJA - Sales, Sheila Cristina Furtado (2008)
This paper has as objective analyze REAJA Rethinking the Education of Teenagers, Young People and Adults, implanted in 1997 in the city of Vitória da Conquista BA, to identify its trajectory since its creation until nowadays. It s interesting to notice that REAJA was introduced to help the initial education of teenagers, young people and adults that didn t have the opportunity to finish their studies in childhood or teens. Trying to contextualize REAJA as a public policy, it was chosen to contextualize the education of young people and adults in Brazil, in Bahia and in the city of Vitória da Conquista, besides characterizing the studied scenery in a demographic and socioeconomic way. It was detached the legislation that guides EJA in Federal and Municipal levels. The investigation process was made by analyzes of documentation collected in the Municipal Secretary of Education in Vitória da Conquista BA, observation at schools, interviews with ex-coordinators of the Programme, SMED´s representative and with teachers that work at REAJA since it was created. Some questionnaires were applied and some data could be collected with students and teachers that work with education to young people and adults in municipal and state public net. Analyzing collected dates, it was a priority to identify positive and negative points of REAJA and the consequences of its trajectory in teaching. Many things were told about teacher s and student s expectation, besides objective and subjective questions of teaching work. Rates about enrolment, pass, recur and truancy and student s profile were collected and discussed. It was noticed that REAJA passed, during its existence for three major levels and each one has its specifications following the expectation of the leading that was in charge of SMED and coordinating the Programme.